Suicides in female prisoners in England and Wales, 1978-2004. - Fazel, S; Benning, R (2009)
We calculated, in narrow age bands, suicide rates for female prisoners compared with the general population between 1978 and 2004. The standardised mortality ratio (SMR) for suicide was 20.7 (95% CI 16.7-25.7), with a higher excess in younger women (<25 years, SMR=40 (95% CI 29-57); >or=25 years, SMR=20 (95% CI 15-26)). There was a trend over time for SMRs to have increased, supporting the need for recent national initiatives for suicide prevention in prisoners.